2021
DOI: 10.1039/d1ra02352g
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cerium doping on Cu–Ni/activated carbon low-temperature CO-SCR denitration catalysts

Abstract: In the process of denitrification, the reaction between NO and CO (NO + CO → N2 + CO2) occurs. There will be a redox reaction between copper, nickel and cerium (Cu2+ + Ce3+ → Cu+ + Ce4+, Ni3+ + Ce3+ → Ni2+ + Ce4+).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…1,2 The selective catalytic reduction of NO x with NH 3 (NH 3 -SCR) is the most efficient and widely used technology for the control of NO x emission. 3,4 Traditional commercial vanadium-titanium catalysts have been used in various industrial elds due to their stability and high efficiency, but industrial application is still restrained by their inevitable drawbacks, including high operation temperature window, poisoning and deactivation of catalyst by deposited alkaline metal, and vanadium poisoning. [5][6][7] Therefore, it is necessary to develop NH 3 -SCR catalysts with excellent denitration activity in low temperature ranges.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The selective catalytic reduction of NO x with NH 3 (NH 3 -SCR) is the most efficient and widely used technology for the control of NO x emission. 3,4 Traditional commercial vanadium-titanium catalysts have been used in various industrial elds due to their stability and high efficiency, but industrial application is still restrained by their inevitable drawbacks, including high operation temperature window, poisoning and deactivation of catalyst by deposited alkaline metal, and vanadium poisoning. [5][6][7] Therefore, it is necessary to develop NH 3 -SCR catalysts with excellent denitration activity in low temperature ranges.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is consistent with the SEM characterization results, as shown in Figure 3b. The XRD spectrum of 4Cu‐2Fe/AC exhibited four characteristic peaks corresponding to copper oxides at 30.62°, 36.86°, 43.6° and 62.46° 14,15 . The detection of iron oxide diffraction peaks was challenging.…”
Section: Resultsmentioning
confidence: 99%
“…The XRD spectrum of 4Cu-2Fe/AC exhibited four characteristic peaks corresponding to copper oxides at 30.62 , 36.86 , 43.6 and 62.46 . 14,15 The detection of iron oxide diffraction peaks was challenging. Based on these results and the microtopography shown in Figure 3c, it was concluded that the numerous dark near-spherical particles were copper oxides adhering to the surface of 4Cu-2Fe/AC.…”
Section: Xrd Characterizationmentioning
confidence: 99%
“…To prepare AC, coconut shell AC particles (coconut shell AC, particle size 10-20 mesh, Henan Gongyi Blue Sky water Purication Technology Co., Ltd) were washed with deionized water to neutral to remove ash and suspended solids, ultrasonicated in a water bath at 60 C for 2 h, and then placed in an airblowing drying oven at 110 C for 24 h aer pumping and ltering. 23 Then, HNO 3 /AC was prepared by impregnating the as-prepared AC in an equal volume of a 30% HNO 3 solution (Zhejiang Shiping Chemical Reagent Factory), followed by reuxing for 2 h in a three-necked ask at 80 C and drying for 24 h in a drying oven at 110 C. 23 Three samples with a mass of 40 g HNO 3 /AC were weighed using an analytical balance, and Cu(NO 3 ) 2 $3H 2 O (AR, Tianjin Kermio Chemical Reagent Co., Ltd) as the precursor was dissolved in a certain amount of deionized water and impregnated for 2 h under ultrasonic vibration at a constant temperature of 60 C, and the samples were then drained and dried at 110 C for 24 h. Finally, the samples were calcined under N 2 protection at 450 C for 4 h and labeled Cu/AC. To prepare Zn-poisoned catalysts with a Zn/Cu molar ratio of 1 : 2, 52 mL ZnCl 2 and ZnSO 4 aqueous solutions were impregnated into Cu/AC catalysts and ultrasonicated for 2 h. 30,31 Then, the poisoned catalysts were drained, dried at 110 C for 24 h, and roasted at 450 C for 4 h under N 2 protection.…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…18,19 Among them, Cu has a high catalytic activity for the CO-SCR reaction and for NO x decomposition, and different Cu species have been proved to be the active sites for NO x adsorption. [20][21][22] Previous studies 23 have demonstrated the excellent performance of a Cu/AC catalyst in CO-SCR denitration; therefore, this catalyst is expected to enable the denitration process at low temperatures. However, the presence of a large amount of dust and metals (Zn, Pb, Ca, As) in the ue gas may block the catalyst pores, leading to catalyst deactivation.…”
Section: Introductionmentioning
confidence: 99%